-4(6y-6)-y=-4(y-5)

Simple and best practice solution for -4(6y-6)-y=-4(y-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(6y-6)-y=-4(y-5) equation:


Simplifying
-4(6y + -6) + -1y = -4(y + -5)

Reorder the terms:
-4(-6 + 6y) + -1y = -4(y + -5)
(-6 * -4 + 6y * -4) + -1y = -4(y + -5)
(24 + -24y) + -1y = -4(y + -5)

Combine like terms: -24y + -1y = -25y
24 + -25y = -4(y + -5)

Reorder the terms:
24 + -25y = -4(-5 + y)
24 + -25y = (-5 * -4 + y * -4)
24 + -25y = (20 + -4y)

Solving
24 + -25y = 20 + -4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4y' to each side of the equation.
24 + -25y + 4y = 20 + -4y + 4y

Combine like terms: -25y + 4y = -21y
24 + -21y = 20 + -4y + 4y

Combine like terms: -4y + 4y = 0
24 + -21y = 20 + 0
24 + -21y = 20

Add '-24' to each side of the equation.
24 + -24 + -21y = 20 + -24

Combine like terms: 24 + -24 = 0
0 + -21y = 20 + -24
-21y = 20 + -24

Combine like terms: 20 + -24 = -4
-21y = -4

Divide each side by '-21'.
y = 0.1904761905

Simplifying
y = 0.1904761905

See similar equations:

| b/8+1/3=19 | | f(x)=3(2+2)-4 | | 4(2-(1/8)p)=(1/4)p-7 | | x^2-10x+21=(x-7)(x+3) | | 6n+6/9=12 | | 3x-5+7=2x-9 | | 15s^2-8s+1=0 | | 9x+5(35-x)=287 | | 6(3x+1)=3x-9X | | 1/4x+4=y | | y^3=-21 | | -12x+2(x-5)+9x=3x-10 | | x+y=15andx-2 | | -3.5=x/7 | | 8b-9y/4b-b-5y/4b | | b-9y/4b-b-5y/4b | | 8b-9y/4b-b-5y/4b=0 | | 2x^3-1-1=0 | | 20+3m+6m=92 | | -52^1/2 | | 11/2d=8 | | 1/5(10x-4)=7 | | -11/2d | | (4x+15)+(-5+2x)+(-10+6x)=360 | | 144/2 | | -[6z-(17z+9)]=9+(10z+1) | | 0=24x^3+20x^2-54x-45 | | 10+25=-5(9x-7) | | 2x-8y-9x+6y= | | 5x+5=49 | | (x-7)(x^2+10x+16)=0 | | 39x+52-14x-35=5x-13 |

Equations solver categories